Results of 25 years of upland rice breeding in Brazil - Breseghello, Flávio; Peixoto de Morais, O; Valle Pinheiro, P; Simoes Silva, C; Maia de Castro, E. da; Guimarães, Elcio Perpétuo; Pereira de Castro, Adriano; Pereira, JA; Matos Lopes, A. de; Utumi, MM; Pereira de Oliveira, J (Wiley, 2011)
The objective of this study was to estimate the results of the upland rice (Oryza sativa L.) breeding program conducted by the Brazilian Agricultural Research Corporation (Embrapa) and collaborators over the period of 1984 to 2009 covering 25 annual steps of improvement. The best lines generated by this program are evaluated in value for cultivation and use (VCU) trials. This study used data from 603 VCU trials conducted in seven Brazilian States. The group of lines entering VCU in each year was taken as a sample of the elite program in that year. Best linear unbiased estimates (BLUEs) of the means of groups were computed, and the regression of the BLUEs on years was taken as an estimate of the efficiency of the breeding program. Traits studied were grain yield (GY), days to flowering (DTF), and plant height (PH). For GY, three phases were described: from 1984 to 1992, the gain for GY was nonsignificant, from 1992 to 2002, the yearly gain was 15.7 kg ha?1 (0.53%), and from 2002 to 2009, the yearly gain was 45.0 kg.ha?1 (1.44%). No evidence of yield plateau was observed. There was a reduction of 0.25 d yr?1 in DTF and 0.52 cm yr?1 in PH, reflecting the change from traditional to modern cultivars. Factors influencing the results of the breeding program in this period are discussed.